Uso da bandagem infrapatelar no desempenho físico e mobilidade funcional de idosas com história de quedas - Carvalho, Isabela Feitosa De (2015)
INTRODUCTION: Some changes occur during the aging process, among which is the postural balance deficit. Sensory information and motor actions are important in the development of postural control, and elderly may have sensorimotor disorders, interfering in postural balance and increasing the risk of falls. It has been shown that manipulation of sensory information in postural control strategy using the soft touch on a hard and stationary surface reduced body sway compared with the situation without touch. OBJECTIVES: To investigate the effect of adding sensory information infrapatellar taping on postural control and physical performance in fallers and non-fallers elderly. METHODS: We evaluated 40 elderly women, divided into two groups: Group 1, consisting of 20 elderly without history of falls, and Group 2, with 20 elderly women with history of falls. The mobility and physical performance were evaluated through Timed Up and Go TUG and Short Physical Performance Battery SPPB tests, respectively, with and without infrapatellar bandage. After checking the normality of the data, comparisons were made using paired and unpaired t test, Wilcoxon test and Mann-Whitney test with p≤0.05. RESULTS: There was significant difference p=0.001 when comparing the TUG in elderly fallers with the use of infrapatellar bandage. There was no significant difference in the use of sensory addition in SPPB. CONCLUSION: The addition of sensory information through the use of infra-patellar taping improves mobility of falling elderly, but not physical performance.